Platelets and coagulation in thrombus formation: aberrations in the Scott syndrome. Issue 141 (May 2016) - van Geffen, Johanna P.; Swieringa, Frauke; Heemskerk, Johan W.M.
Abstract: Platelets play key roles in thrombosis and hemostasis by forming aggregates and providing a procoagulant surface, at which thrombin is generated and fibrin fibers are formed. Here we present an overview of the different mechanisms how platelets orchestrate coagulation processes in thrombus formation in thrombosis and hemostasis. Parts of these are via Ca 2+ -dependent activation responses, leading to phosphatidylserine exposure; swelling to form balloons with increased binding of coagulation factors; and calpain-mediated integrin αIIb β3 cleavage and inactivation. Other mechanisms are secretion of (anti) coagulation factors, and αIIb β3 -mediated thrombus retraction, and clot retraction. In a thrombus, coagulation factors are found at both platelets and fibrin fibers. Many of the procoagulant platelet activities are altered in the Scott syndrome.